Combination of noninvasive methods in diagnosis of infertile women with minimal or mild endometriosis, a retrospective study in China. Issue 31 (August 2019) - Yu, Huaying; Li, Baijia; Li, TinChiu; Zhang, Songying; Lin, Xiaona
Abstract : Abstract: This study means to investigate a combination of noninvasive methods in diagnosis of minimal or mild endometriosis expecting to narrow down the range of laparoscopic exploration for female infertility. It is a retrospective case control study of totally 447 patients suspected unexplained infertility before surgery were eligible from May 2012 to February 2017. Of these, 299 patients were laparoscopy-proved minimal or mild endometriosis group, the remaining 148 patients served as control group (normal pelvis). Preoperative age, duration of infertility, type of infertility, body mass index, baseline follicle-stimulating hormone, anti- Müllerian hormone, serum CA125, clinical symptoms, findings on vagino-recto-abdominal examinations and pregnancy prognosis had been recorded. Every variable and their combinations were evaluated. Any single factor had limited diagnostic value. The cut-off value for CA125 was 19.25 IU/L. Parallel testing had a higher sensitivity at 81.3%. Serial tests of vagino-recto-abdominal examination combined with dysmenorrhea or positive CA125 got reasonable sensitivity (51.4% and 49%), remarkable high specificities (95.7% and100%) and Positive Predictive Value (96.4% and 100%). Multivariate logistic regression identified the following factors in decreasing order of importance: (1) vagino-recto-abdominal examinations, (2) CA125, (3) dysmenorrhea, their ORs being 16.148, 3.796, and 2.809, respectively. The spontaneous pregnancy rate (50.8%) in minimal or mild endometriosis was higher than control (35.6%, P = .043). A combination of noninvasive diagnostic methods had certain preoperative diagnostic value of minimal or mild endometriosis, which might benefit some patients from avoiding laparoscopic surgery.